2018
DOI: 10.1021/acssuschemeng.7b01456
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method of Recycling of CFRP Waste Using Peracetic Acid

Abstract: We report a one-step oxidative method for the recycling of carbon fiber-reinforced polymer (CFRP) composite waste and the recovery of carbon fiber and the epoxy resin by treatment with peracetic acid (PAA) formed in situ from a mixture of acetic acid and hydrogen peroxide. The surfaces of the recovered carbon fibers were clean, and the tensile strength was comparable to that of the virgin fibers. A higher resin decomposition ratio of 97% could be achieved for the epoxy matrix under mild reaction conditions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 33 publications
0
73
0
Order By: Relevance
“…Two different control experiments using solutions of pure H 2 O 2 and pure TA (5 M) were also performed. Afterwards, the remaining WCP, which mainly consisted of recycled GFs, was washed with acetone in an ultrasonic cleaner for 5 min, followed by drying at 60 • C. The decomposition yield (D y ) was calculated according to the following Equation (1) [38]:…”
Section: Recycling Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Two different control experiments using solutions of pure H 2 O 2 and pure TA (5 M) were also performed. Afterwards, the remaining WCP, which mainly consisted of recycled GFs, was washed with acetone in an ultrasonic cleaner for 5 min, followed by drying at 60 • C. The decomposition yield (D y ) was calculated according to the following Equation (1) [38]:…”
Section: Recycling Processmentioning
confidence: 99%
“…This implies that only the reaction of TA and H 2 O 2 under microwave irradiation provides an oxidation medium suitable for epoxy matrix decomposition. It can be discussed that the reaction of H 2 O 2 and TA can produce various reactive species (e.g., organic peroxides) which can decompose epoxy resin possibly through C-N bonds cleavage [23,33,37,38]. Moreover, to investigate the role of microwave irradiation, an H 2 O 2 /TA solution without WCP was also treated under microwave irradiation, which can only raise the temperature up to~70 • C within 1.5 min irradiation.…”
Section: Recycling Process Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The single fibre tensile test only showed a 2% tensile strength loss compared to the vCF after a 10 °C process temperature increase. In a recent study, Das et al [91] showed a 97% resin decomposition ratio from a single-stage oxidation process using an aqueous mixture (AM) of peracetic acids. The rCF retained 94% of its original strength.…”
Section: Recycling Using Mild Conditionsmentioning
confidence: 99%
“…Chemical reclamation methods use reactive, solution-based processes to break down the matrix material (e.g., acid digestion, solvolysis, and supercritical fluid solvolysis). Acid digestion uses a variety of highly corrosive reactant systems (e.g., nitric acid [8,9], sulphuric acid [10], acetic acid [11,12], and some alkalis [13]), to degrade the thermoplastic matrix at low temperatures (<150 • C). Solvolysis methods use less hazardous solvents and catalysts, but suitable reactivity is achieved by operating at higher temperatures (200-300 • C) to afford a suitable reactivity for a specific polymer [14].…”
Section: Introductionmentioning
confidence: 99%